COMPUTATIONAL MODELING OF RTM AND LRTM PROCESSES APPLIED TO COMPLEX GEOMETRIES - Porto, J. da S.; Letzow, M.; dos Santos, E. D.; Amico, S. C.; Souza, J. A.; Isoldi, L. A. (Revista de Engenharia Térmica, 2012)
Light Resin Transfer Molding (LRTM) is a variation of the conventional manufacturing process known as Resin Transfer Molding (RTM). In general terms, these manufacturing processes consist of a closed mould with a preplaced fibrous preform through which a polymeric resin is injected, filling the mold completely, producing parts with complex geometries (in general) and good finish. Those processes differ, among other aspects, in the way that injection occurs. In the RTM process the resin is injected through discrete points whereas in LRTM it is injected into an empty channel (with no porous medium) which surrounds the entire mold perimeter. There are several numerical studies involving the RTM process but LRTM has not been explored enough by the scientific community. Based on that, this work proposes a numerical model developed in the FLUENT package to study the resin flow behavior in the LRTM process. Darcy’s law and Volume of Fluid method (VOF) are used to treat the interaction between air and resin during the flow in the porous medium, i.e. the mold filling problem. Moreover, two three-dimensional geometries were numerically simulated considering the RTM and LRTM processes. It was possible to note the huge differences about resin flow behavior and filling time between these processes to manufacture the same parts.